Răspuns:
[tex]a) \sqrt{ {(x - 5)}^{2} } = 2 \\ |x - 5| = 2 \\ x - 5 = 2 \: \: \: x = 7 \\ - (x - 5) = 2 \: \\ - x + 5 = 2 \: \: - x = - 3 \: \: x = 3[/tex]
[tex]b) \sqrt{ {(x - 5)}^{2} } + 5 | - x + 5| = 0 \\ |x - 5| + 5 | - x + 5| = 0 \\ x - 5 + 5 \times ( - x + 5) = 0 \\ x - 5 - 5x + 25 = 0 \\ - 4x = - 20 \: \: x = 5 \\ - (x - 5) + 5 \times (x - 5) = 0 \\ - x + 5 + 5x - 25 = 0 \\ 4x - 20 = 0 \: \: 4x = 20 \: \: \: x = 5[/tex]
[tex]c) \sqrt{ {(5x - 3)}^{2} } = \sqrt{ {(3x + 4)}^{2} } \\ |5x - 3| = |3x + 4| \\ 5x - 3 = 3x + 4 \\ 2x = 7 \: \: x = \frac{7}{2} \\ - 5x + 3 = - 3x - 4 \\ - 2x = - 7 \\ x = \frac{7}{2} [/tex]